2017
DOI: 10.1534/g3.116.037622
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions Associated with Tolerance to Freezing Stress and Snow Mold in Winter Wheat

Abstract: Plants grown through the winter are subject to selective pressures that vary with each year’s unique conditions, necessitating tolerance of numerous abiotic and biotic stress factors. The objective of this study was to identify molecular markers in winter wheat (Triticum aestivum L.) associated with tolerance of two of these stresses, freezing temperatures and snow mold—a fungal disease complex active under snow cover. A population of 155 F2:5 recombinant inbred lines from a cross between soft white wheat cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 45 publications
6
52
0
Order By: Relevance
“…Naruoka et al (2011) reported a QTL for increasing tiller numbers on chromosome 6B (QTn.mst-6B) between markers gwm 88 and gwm 193 in spring wheat, which is located on centromere region. Kruse et al (2017) also reported QTL for snow mold resistance on chromosome 6B. Based on our results, the QTL for snow mold resistance detected on chromosome 6B between markers wmc 104 and barc 136 from Ibis was also on centromere region flanking QTn.mst-6B, which indicated that both QTL are located close regions.…”
Section: Discussionsupporting
confidence: 68%
“…Naruoka et al (2011) reported a QTL for increasing tiller numbers on chromosome 6B (QTn.mst-6B) between markers gwm 88 and gwm 193 in spring wheat, which is located on centromere region. Kruse et al (2017) also reported QTL for snow mold resistance on chromosome 6B. Based on our results, the QTL for snow mold resistance detected on chromosome 6B between markers wmc 104 and barc 136 from Ibis was also on centromere region flanking QTn.mst-6B, which indicated that both QTL are located close regions.…”
Section: Discussionsupporting
confidence: 68%
“…Maximum likelihood mapping, which used five rounds of optimization, chain lengths of 1000, and termination after 100,000 chains without improvement, was used to determine the distances within linkage groups. These linkage map construction methods are also described in the supplemental materials of Kruse et al (2017). All published QTL were detected via composite interval mapping with WinQTL Cartographer version 2.5 software (Wang et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Within 24 h of low-temperature treatment, the expression of TaSnRK2.7 gene reached the highest level. The overexpression of TaSnRK2.7 significantly increased the resistance of Arabidopsis to drought, salt, and low-temperature stress (Zhang et al, 2010 Although tolerance to subzero temperatures is often critical to winter survival, the genetic dissection of freezing tolerance of wheat has been rather limited (Kruse et al, 2017). The Vrn loci located on chromosome 5 are known to have pleiotropic effect to affect both the vernalization response and frost hardiness of winter wheat (Koemel et al, 2004).…”
Section: Key Signaling Pathways Participated In Freezing Resistance Imentioning
confidence: 99%